The rebranding of ZANU PF in the new political dispensation between the period of December 2017 and March 2018: a case of ZBC news online. - Ziwewe, Tapiwa (Midlands State University, 2019)
The research seeks to explore how ZBC news online is rebranding the new political dispensation. Thus the study looks at how ZBC framed of political news in the new dispensation especially the rebranding of the Zimbabwe African Nationalism Patriotic Front (ZANU PF). The scope of the study is December 2017 to March 2018. The study is qualitative in nature as it applies the use of archival collection and interviews, Critical Discourse Analysis (CDA) and thematic analysis were applied and it was discovered that there was a positive framing of the new political dispensation and political economy of ZBC has got a bearing in content generation, distribution and consumption and this is the reason why ZBC was involved in the rebranding of ZANU PF after the ouster of Robert Mugabe.